Reflections on current practices of group work learning at the University of Limpopo, South Africa : towards a refined contextual approach - Modipane, Mpho Calphonia (My University, 2020)
Group Work Learning (GWL) has, over the past thirty years, grown in popularity as a pedagogy in Higher Education across the world, and has widely been documented as a more effective pedagogy in comparison to individualistic learning. However, research studies also warn against the uninformed use of GWL and the negative results thereof. Within popular modes of GWL such as cooperative learning, team because their use has proven to yield success and positive results. It is within this context that the study sought to reflect on the practices of GWL at the University of Limpopo with the view to arrive at refined contextual approaches- approaches that would be reflective and context driven. The study adopted a qualitative research approach, which is anchored in the interpretive research paradigm, and employed a descriptive and exploratory case study design to address the existing knowledge gaps. Semi-structured interviews with eight lecturers from the four faculties at University of Limpopo, observations with eight student groups and informal conversations with the eight student groups were used to collect data for the study. The key findings of the study were as follows: 1) Practitioners in the study did not employ any particular elements, guidelines, principles, models or theories to underpin their use of GWL as a teaching and learning strategy and 2) Individual and group accountability, poor participation and group dynamics remained a challenge in the use of GWL. The additional sub-findings were: 1) The intended or required learning was clearly articulated but focused mainly on learning content and minimally on skills development, values and attitudes, 2) Group formation and group size varied from group to group depending on class size and did not consider context. 3) Practitioners thought there was a need for the improvement of GWL, 4) The study identified challenges and possibilities for improvement. Based on these findings, I propose a guided, reflective and contextual approach to GWL that is cyclic in character, places the reflectiveness and context of the practices at the center of the process and in which the approach further connects the practices to all the other components that are key to GWL, namely: clear intended learning outcomes that are inclusive of skills, values and attitudes; clear task instruction; elements or guidelines underpinned by relevant group learning theories or models; as well as clear measures to xiii foster accountability. Group formation and group size based on a clear rationale, as well as continuous reflection on the process with a view to improving and refining the practices. Such an approach is likely to provide the student groups with some framework on how to learn together and complete their tasks/assignments and projects in a manner which is accountable.
Thesis (Ph.D. (Curriculum Studies)) -- University of Limpopo, 2020
Keywords: Reflection; GWL; Cooperative learning; Team-based learning; Collaborative learning; Group work in education; Team learning approach in education; Education, Cooperative